Hating Women: A Constitution of Hate in Plain Sight - Brayson, Kimberley (Journal of interpersonal violence, 2024)
In April 2023, the U.K. government announced that misogyny would not be categorized as a hate crime stating that this “may prove more harmful than helpful.” This article argues that before and beyond hate crime, misogyny, understood as the hatred of women (from the Greek misein [hate] gynae [women]), is the foundational logic of our legal, social, and political order in the west. This constitution of hate relies on the active dehumanization, exploitation, and ownership of women’s bodies by the institution of white men through making women the object of the “colonization of the everyday.” This exhausting hatred is enacted through repetitive, unceasing, and everyday violence toward women. Simply put, patriarchal, colonial, capitalist democracy is only sustained through violence against women. Hating women is, therefore, not a pathology of society but rather is the necessary existence condition of our legal-political constitution, clear to see yet hiding in plain sight. Misogyny ensures the precarity of women’s bodies and women’s status as trespassers in everyday spaces that are deliberately always already misogynistic. Given the foundational nature of misogyny, did the government have a point in excluding endemic violence against women from hate crime as “more harmful than helpful?” Is hate crime merely constitutive of a cultural matrix of misogyny? This paper enacts a decolonial feminist prism to disrupt the cultural condition of misogyny by thinking hate crime together with legal-political constitutional and cultural change. The paper explores violence against women set against the historical emergence of misogyny from Greek dehumanization, to medieval persecution of “witches,” the muzzling and banning of women from public spaces, Shakespeare’s “Taming,” to contemporary femicide rates. Interrogating hate crime through this prism offers nuanced routes for how to disrupt the legal-political constitution of misogyny that is neither hidden nor new. Misogyny is enduring.